Leading Change for Sustainable Development Through Strategic Project Management: A Case Study on Change Management - Randeree, K; Iqbal, A (Common Ground Publishing, 2009)
Public sector organisations face a momentous task of constant change and upgrade to their services in today’s dynamic and hyper turbulent market place. Owing to the hyper active nature of the market place, the pace of change has never been greater than in the current business environment and is becoming a constant feature of organisational life. Coupled with massive economic expansion, increased globalisation and massive transnational flow of information, there is colossal pressure on public sector organisations to relentlessly instigate change. This paper focuses on one such change, the establishment of an automated road tolling system wherein the organisation (roads and traffic agency) is faced with the task of resolving the traffic woes of the city of Dubai in the United Arab Emirates (UAE) and is working towards the integration of the entire road and transport network. The aim of this paper is to examine ways of improving the effectiveness of public sector organisations to manage change. This was explored by investigating how the road and traffic agency is managing change, especially change related to the implementation of advanced technology, evaluate the consequences of this change on the existing network and stakeholders and to appraise the management strategy deployed to address the transport network. The findings of this paper indicate key emerging issues adversely impacting the change approach deployed. These include prioritisation issues, timing of the change activities, time allotted to the change activities and issues pertaining to monitoring and feedback of change.